Effect of Multi-Ingredient Supplement Containing Satiereal, Naringin, and Vitamin D on Body Composition, Mood, and Satiety in Overweight Adults. (2nd November 2018) - Gonzalez, Adam M.; Sell, Katie M.; Ghigiarelli, Jamie J.; Spitz, Robert W.; Accetta, Matthew R.; Mangine, Gerald T.
ABSTRACT: The purpose of this investigation was to examine the effects of 28 days of a dietary supplement on body composition, mood, and satiety in overweight adults. Twenty healthy adults (25.5 ± 3.8 years; 87.3 ± 20.7 kg; 169.9 ± 10.6 cm; 29.9 ± 5.1 body mass index) participated in this randomized, double-blind, placebo-controlled investigation. Ten participants were provided with a dietary supplement containing 178 mg satiereal, 100 mg naringin, and 2, 000 IU vitamin D3 daily (SUPP), and ten participants were provided a placebo (PL) for 28 days. Baseline (PRE) and post (POST) assessments included body mass, BMI, and waist circumference measures. In addition, participants provided self-reported food records and completed study questionnaires twice weekly. Questionnaires consisted of profile of mood states, visual analog scales, modified trait food-cravings questionnaire, and a modified state food-cravings questionnaire. No significant differences were noted between groups for total calorie or macronutrient intake ( p = 0.65–0.92), body mass ( p = 0.34), BMI ( p = 0.24), or waist circumference measures ( p = 0.56–0.94). In addition, no significant differences between groups were observed for mood states, subjective measures of food cravings, or feelings of anxiety, fullness, bloating, hunger, craving, and stress ( p >.05). In conclusion, 28 days of a dietary supplement containing satiereal, naringin, and vitamin D3 did not have any detectable beneficial effects on body-weight management.